Effects and limits of highly efficient nucleating agents in thermoplastic polyurethane. (10th October 2019) - Maiz, Jon; Fernández-d'Arlas, Borja; Li, Xinye; Balko, Jens; Pöselt, Elmar; Dabbous, Raphaël; Thurn-Albrecht, Thomas; Müller, Alejandro J.
Abstract: In this work, we have investigated the effects of several nucleating agents on crystallization kinetics and morphology in a thermoplastic polyurethane (TPU). For one specific nucleating agent (denoted NAII), the nucleation efficiency was almost 100%; this means that this nucleating agent is as efficient as TPU's self-nuclei. Adding NAII largely increases the crystallization temperature (around 60 °C), the melting temperature, the overall crystallization kinetics, the lamellar thickness, and the crystallinity of TPU. All these remarkable changes (which could improve the mechanical properties) only occur if the material is cooled from the melt below a critical cooling rate. When the cooling rate is higher than this critical value (approximately 200 °C/min), the nucleating action of the nucleating agents (or even of the TPU self-nuclei) is effectively lost, and the crystallization occurs as in neat TPU, but with an important reduction in crystallinity. The practical consequence is that if the TPU employed here is used in injection molding, the nucleating agents of this study can only be effective if they are cooled down at rates below the critical value, i.e., in practice only for samples that have a sufficiently large thickness. Graphical abstract: Image 10 Highlights: A nucleating agent (NA) with almost 100% efficiency for commercial TPU was found. The efficiency of NAs is lost when TPU/NA blends are cooled faster than a critical rate. The highly efficient NA increases the melting point of TPU substantially, as well as its lamellar thickness. The crystallization kinetics can also be greatly enhanced by efficient NAs.